Spring MVC beginner's guide : your ultimate guide to building web applications using all the capabilities of Spring MVC - G, Amuthan (Community experience distilled., 2014)
Chapter 3: Control Your Store with Controllers; Defining a controller; Time for action - adding class-level request mapping; The role of a controller in Spring MVC; Handler mapping; Using URI template patterns; Time for action - showing products based on category; Using matrix variables; Time for action - showing the products based on filter; Understanding request parameters; Time for action - adding the product details page; Time for action - implementing a master detail view; Summary; Chapter 4: Working with Spring Tag Libraries; Serving and processing forms